The economy: the invisible hand and public vices - Carranza Elguera , Víctor Humberto (2011)
Most of our economists affirm that we are already a western and modern country and they try to convince us, in a way that is not consistently explained to us, that Peruvian society has been empowered within the framework of liberal capitalism, reinforcing this position in a national state and in the positivist reason of science. In the present text we affirm that these factors have indeed been installed in Peru; but in a defective way. Worse still, in order to achieve this, the use of exclusionary, instrumentalist and totalitarian methods was not spared in the face of other, non-liberal, non-scientific and non-Europeanizing discourses.